ARTIFICIAL INTELLIGENCE: THE FUTURE OF LABOUR AND EMPLOYMENT - Gasda, Élio (Asian Horizons, 2020)
There are two principal currents of opinion about the future of labour: those who think the advance of Artificial Intelligence (AI) will destroy professions, provoking mass technological unemployment, and those who think that, as has happened before in the history of labour, new technologies like AI will create new jobs. The fact is that AI will have a profound impact in the world of labour. The article is organized in three parts: first describing AI in the context of the Fourth Industrial Revolution; then exploring AI’s potential threats and opportunities in the world of labour. The text is concluded with an ethical question: Does AI offer the possibility of thinking about a new paradigm of labour and of civilization? The Fourth Industrial Revolution must be put at the service of humanity and not of the market. The choices of the present will dictate the directions of the future of labour.